Early pregnancy diagnosis in cattle and buffaloes from milk - LAKHCHAURA, B D; CHAVAN, SEEMA; UMAPATHI, V (The Indian Journal of Animal Reproduction, 2023)
An immunodiagnostic kit has been developed for the early pregnancy diagnosis in cattle and buffaloes, based on the detection of progestrerone in the milk by dipstick EIA method. Discriminatory level was placed at 5-ng/ml progesterone for pregnant animals and I ng/lml for non-pregnant animals. The accuracy for positive diagnosis was 90-92% while non-pregnancy was diagnosed with 100°/c, accuracy. The pregnancy can be diagnosed between 18-24 days of post insemination by this method. All the components in the kits are supplied in lyophilized form for a prolonged shelf-life and convenience for field application. Assay is well suited for routine testing particulariy in cattle and buffaloes since milk sampling is easy and doesn’t disturb the animal.